AN ANALYSIS OF GRAMMATICAL ERRORS AND THE CAUSES OF ERRORS IN STUDENTS’ ANALYTICAL EXPOSITION TEXT - Asmah - Salaema (Jurnal Penelitian, Pendidikan, dan Pembelajaran, 2021)
This research was aimed to find out the types of grammatical errors made by EFL senior high school students in writing an analytical exposition text, the causes of their grammatical errors in writing the text, and their attitude towards errors correction suggested by their teacher. This study applied descriptive qualitative research design. The data were taken from the students’ writing product purposively and a semi-structured interview with 10 guided questions. The highest frequency of students’ grammatical errors was omission which consisted of 53.40% errors, the second was misformation which consisted of 38.63%, and then the third was addition which consisted of 5 errors or 5.68%, and the last was misordering which consisted of 2.27%. The causes of errors are resulted from interlingual, and intralingual transfer. Besides, the findings in the interview session suggest that the students considered the teacher’s errors correction influenced their recognition in writing. However, the teacher’s written corrective feedback should be combined with oral feedback to help the students have better understanding towards the feedback given by teacher.